Titul "Syn Čelovečeskij" v Evangelii ot Ioanna: kritičeskij obzor sovremennych predstavlenij = Son of Man in the Gospel of John: a Critical Overview of Some Contemporary Perspectives - Kirianov, Viktor (Bogoslovskie razmyšlenija, 2018)
In this paper, different theologian’s opinion will be viewed concerning the title "Son of Man" in John. It is believed that Jesus didn’t introduce this title, its roots are found in the OT. Passages like in Dan.7, Ezek., 1 Enoch 37-71 mention "the Son of Man" term, so these passages where probably the source for Jesus to use "the Son of Man" title and probably the Christian community used this title for Jesus. The supporters of alternative position believe that Jesus mentioned the Son of Man as somebody else. All these views will be analyzed to find out if Jesus used the OT title for Himself or He introduced it. The meaning of the title will be found in the article. John’s Gospel gives an important role to the question of Jesus’ "lifting up". Another question will be discussed - did John spoke about the ascend - descend of the Son of Man, about the exaltation of the Son of Man or about Jesus’ crucifixion and death. Another issue is that several titles merge in the Forth Gospel to show Jesus Messianic origin, to show that He as the Son of Man is also the Son of God. In the beginning of each section, the argument will be offered, than the opinions of some theologians will be given. At the end of the section the author’s position will be offered.